Religious Tolerance of the Young Generation: Religious Convergence in Education - Supriyanti, Iin; Huda, Hairul (Proceeding International Conference on Religion, Science and Education, 2025)
The purpose of this study was to determine the importance of religious tolerance among the younger generation in Indonesia, focusing on the practice of religious moderation in Dusun Sumberejo, Jombang Regency. This study used a descriptive qualitative approach, observing the interaction between students of Islamic Boarding Schools and church congregations who share physical space. The results showed that character education and empathy play an important role in building attitudes of tolerance between religious communities. Through interfaith training programs, young people are taught to respect differences and contribute to joint activities, which create a harmonious environment. These findings emphasize that religious moderation can be achieved through dialogue, cooperation, and the development of empathy, and is an important step in forming a peaceful and civilized society.